Celebrating Tolerance in Diversity: A Perspective of Living Values Education (LVE) - Nst, Mhd Imam Zuhdi; Kurniawan, Vicky (Institut Agama Islam Negeri Kerinci, 2023)
Abstract The issue in this research lies in a multicultural society with heterogeneous characteristics, leading to several problems of intolerance and a lack of application of universal values within the community, such as a deficiency in religious community comfort. The objective of this research is to assess the state of religious tolerance in Pelayang Raya Village, Sungai Bungkal, Sungai Penuh City, and the implementation of religious tolerance values in the village, viewed from the perspective of Living Values Education (LVE). The research adopts a qualitative approach with a phenomenological focus. Data collection techniques involve observation, interviews, and documentation. Data analysis is conducted through data reduction, data presentation, and verification of conclusions. The findings reveal instances of intolerant behavior in the community of Pelayang Raya Village, resulting in issues. The solution lies in the community prioritizing and more actively applying and embodying religious tolerance values, fostering a harmonious, secure, and peaceful community. Keywords: Religious Tolerance, Living Values Education, Sungai Penuh